Propuesta para el Diseño y Planeación de la cadena de suministro en el sector de BPO (Business Process Outsourcing) (2021)
This work is about the development of a proposal for the design and planning of the Supply Chain for BPO companies in the Record Management business line, a sector that due to market conditions requires a more adequate identification of the composition and behavior of the supply chain in order to be more competitive and be able to response with capacity at the time of projects execution. This proposal is based on the analysis of the different performance evaluation models that allow the study of each of the links in the chain and their interaction, as well as the study of the impact of the stakeholders that can contribute to the proper use of resources and the improvement on the information use.